1999
DOI: 10.1038/sj.bjc.6690740
|View full text |Cite
|
Sign up to set email alerts
|

Minimally-invasive debulking of ovarian cancer in the rat pelvis by means of photodynamic therapy using the pegylated photosensitizer PEG-m-THPC

Abstract: Summary Interstitial photodynamic therapy (PDT) using the pegylated photosensitizer PEG-m-THPC was evaluated as a minimally-invasive procedure to selectively debulk unrespectable pelvic ovarian cancer (NuTu-19) in immunocompetent rats. To assess tumour selectivity, PEGm-THPC at dosages of 0.3, 3.0 and 30 mg kg -1 body weight was administered intravenously to 30 rats 4 weeks following tumour induction. Eight days later laser light at 652 nm and optical doses ranging from 100 to 900 J cm -1 diffuser-length was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…Considering that this PDT dose induces maximal damage to all tissues, this steady temperature increase may be a sign of a systemic toxic reaction. This assumption can be supported by a previous finding where two of four tumor-bearing rats died during PDT with 30 mg/kg PEG-m-THPC activated with 900 J/cm diffuser length (2). Since the temperature never exceeded 39ЊC, damage to tissue was not induced by hyperthermia but by a PDTmediated phototoxic reaction.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Considering that this PDT dose induces maximal damage to all tissues, this steady temperature increase may be a sign of a systemic toxic reaction. This assumption can be supported by a previous finding where two of four tumor-bearing rats died during PDT with 30 mg/kg PEG-m-THPC activated with 900 J/cm diffuser length (2). Since the temperature never exceeded 39ЊC, damage to tissue was not induced by hyperthermia but by a PDTmediated phototoxic reaction.…”
Section: Discussionsupporting
confidence: 61%
“…uated (1,2). PDT is based on the preferential uptake and/or retention of a photosensitizer by malignant tissues (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant delay in tumor regrowth was achieved following meta-tetrahydroxyphenylchlorin-mediated intraperitoneal PDT and a toxicity study has determined the maximum tolerable light dose of ALA-mediated intraperitoneal PDT. (7,8) Hornung et al (9,10) showed that intraperitoneal PDT, as a minimally invasive procedure, could selectively debulk unresectable pelvic ovarian cancer in immunocompetent rats using the pegylated photosensitizer PEG-m-THPC, which was confirmed to be highly targeted to ovarian cancer in a rat model. Several clinical trials using first-generation photosensitizer dihematoporphyrin ether and porfimer sodium showed the therapeutic effects of PDT in treating peritoneal malignancy including ovarian cancer.…”
mentioning
confidence: 99%
“…De nombreuses études expérimentales animales rapportent l'efficacité de la PDT dans la carcinose péritonéale d'origine ovarienne [8,19,49,50]. Dans un modèle animal de carcinose péritonéale d'origine ovarienne, Hornung et al ont montré une efficacité significative en terme de survie, par rapport aux animaux témoins, de la PDT réalisée avec du Foscan W administré par voie intraveineuse, ou un de ses dérivés [49,50]. Une étude de Major en 2002 a permis de déterminer la dose thérapeutique maximale d'ALA (50 mg/kg) administrée par voie intrapéritonéale (IP) chez le rat.…”
Section: Carcinose Pé Ritoné Ale D'origine Ovarienneunclassified